1998
DOI: 10.1080/01635589809514732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid on DNA adduct formation of PhIP and IQ after bolus administration to female F344 rats

Abstract: Meats cooked at high temperatures contain mutagenic heterocyclic amines such as 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) and 2-amino-3-methylimidazo[4,5-f]quinoline (IQ). In female Fischer 344 rats, IQ is a multiorgan carcinogen, whereas PhIP induces mammary adenocarcinomas. For IQ and PhIP, N-hydroxylation, catalyzed by microsomal cytochrome P-450 1A1 and/or 1A2, and then esterification, especially O-acetylation, are the principal steps leading to DNA adduct formation. Conjugated linoleic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that CLA does not alter CYP expression. 43,44) However, it is possible that PGO may affect liver CYPs, including CYP2E1, which activates AOM, since dietary CLN suppressed AOM-induced ACF when fed during AOM exposure. 25) The results described here suggest that dietary feeding of PGO suppressed progression of these lesions through adenoma to malignant neoplasm in the post-initiation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CLA does not alter CYP expression. 43,44) However, it is possible that PGO may affect liver CYPs, including CYP2E1, which activates AOM, since dietary CLN suppressed AOM-induced ACF when fed during AOM exposure. 25) The results described here suggest that dietary feeding of PGO suppressed progression of these lesions through adenoma to malignant neoplasm in the post-initiation phase.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported a protective activity of CLA against HCA-induced carcinogenesis by measuring changes in HCA-DNA adduct levels. CLA was found to reduce the formation of PhIP-DNA adducts in the colon, 2-amino-3-methylimidazo[4,5-f]quinoline (IQ)-DNA adducts in the mammary gland of female rats [Josyula and Schut 1998], and DNA adducts and aberrant crypt foci induced by IQ in the colon of male rats [Liew et al, 1995]. Of particular interest is that the protective efficacy of CLA is sex-related, as shown by Zu and Schut [1992].…”
Section: Introductionmentioning
confidence: 98%
“…Presumably, chemical compounds responsible for activation of CYP 1A1/1A2 in the liver and intestine enter the body with food [10] or were formed in the gastrointestinal tract as a result of vital activity of some bacteria.…”
Section: Resultsmentioning
confidence: 99%